Kombinasi Kinesio Tapping dan Yoga Cat Cow Pose Efektif Menurunkan Ketidaknyamanan Punggung Bawah Pada Ibu Hamil Trimester III - Niken Wahyu Hidayati; Noor Rofiatus S; Sri Yunita Suraida Salat; Siti Sarti; Puput Kurnia Sari (Fakultas Ilmu Kesehatan, 2022)
Back discomfort for pregnant women at the end trimester do to changes in the musculoskeletal system. This is causes increase volume of the uterus and the mother's weight so that the center of gravity leans forward to adjust the shape of the pregnant woman's posture. First treatment for the mother's lower back discomfort is kinessiotapping and cat cow yoga pose. This study aims to analyze the effectiveness of using kinesiotapping and cat cow yoga against lower back pain in third trimester pregnant women at the Kalinyamatan Health Center, Jepara. This study used a two-group pre-test-post-test group design experimental design. The sample includes 20 pregnant women with lower back pain by random sampling technique. Kinesiotapping and cat cow yoga pose were given 30 minutes for five days. The results of the independent t test statistical test with a p value <0.05, means that kinesio tapping and cat cow yoga are effective in reducing low back pain in third trimester pregnant women.